Community, Market and State in Development 2010
DOI: 10.1057/9780230295018_12
|View full text |Cite
|
Sign up to set email alerts
|

Promises and Realities of Community-Based Agricultural Extension

Abstract: Notices 1 Effective January 2007, the Discussion Paper series within each division and the Director General's Office of IFPRI were merged into one IFPRI-wide Discussion Paper series. The new series begins with number 00689, reflecting the prior publication of 688 discussion papers within the dispersed series. The earlier series are available on IFPRI's website at http://www.ifpri.org/publications/results/taxonomy%3A468. 2 IFPRI Discussion Papers contain preliminary material and research results. They have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 30 publications
1
64
0
3
Order By: Relevance
“…The challenges faced by public seed companies involved in these tasks have already been described above. Public agricultural extension services are also facing numerous governance challenges which are well documented in the literature (see, e.g., Feder et al 2010). With regard to seed promotion, the scale and complexity of extension service provision commonly presents the biggest problem (cf.…”
Section: State Failurementioning
confidence: 99%
“…The challenges faced by public seed companies involved in these tasks have already been described above. Public agricultural extension services are also facing numerous governance challenges which are well documented in the literature (see, e.g., Feder et al 2010). With regard to seed promotion, the scale and complexity of extension service provision commonly presents the biggest problem (cf.…”
Section: State Failurementioning
confidence: 99%
“…The main criticism suggested that CBWs are not always sufficiently knowledgeable and equipped to pass on information to others adequately (CBW, 2007). In their review of community-based agricultural extension approaches, Feder et al (2010) concluded that communities can also fail in extension delivery. Elite capture, for example, was a major constraint, as well as limited availability of competent service providers, deep-seated cultural attitudes that prevent effective empowerment of farmers and difficulties in implementing farmers' control of service providers' contracts.…”
Section: Institutional Pluralism Empowerment and Community-based Extmentioning
confidence: 99%
“…About 80 percent of the extension services are publicly funded and delivered by civil servants, justified by the view that many aspects of agricultural knowledge diffusion are 'public goods'. However, there is a general consensus that the performance of extension services has been disappointing (Anderson, 2007;Feder et al, 2010).…”
Section: Challenges Of Agricultural Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, sustainability of CrFS activities after the end of the BINDS program was a challenge identified by all the stakeholders (Oxfam 2015), which is a common critic of FFS and community-based approaches in literature (see Anderson and Feder 2004;Swanson 2008;Feder et al 2010;Swanson and Rajalahti 2010;Sherwood et al 2012;Ensor et al 2014). This research notes that financial Whatever the approach, diffusion of CrFS, institutional strategies (see Table 7 a.…”
Section: Barriers To Adoption Of Climate-smart Interventionsmentioning
confidence: 99%